Functional Neuroimaging Correlates of Aggression in Psychosis: A Systematic Review With Recommendations for Future Research - Widmayer, Sonja; Borgwardt, Stefan; Lang, Undine E.; Stieglitz, Rolf-Dieter; Huber, Christian G. (Frontiers in Psychiatry, 2019)
Background and methods. Aggression in psychosis is clinically important. We systematically compiled the evidence on functional correlates of aggression in psychosis searching EMBASE, ScienceDirect and PsycINFO until September 2017. We included studies reporting functional brain imaging correlates of aggression comparing: 1) affective or non-affective psychosis groups with a history of violence or with aggression operationalized using questionnaires , 2) affective or non-affective psychosis groups with a history of violence or with aggression operationalized using questionnaires to controls, 3) affective or non-affective psychosis groups with a history of violence or with aggression operationalized using questionnaires to controls with diagnoses other than affective or non-affective psychoses. We applied no language restriction and required patients to have a DSM or ICD diagnosis of affective or non-affective psychosis. Results. Our sample consisted of 12 studies with 334 patients and 113 controls. During n-back tasks, violent (VS) as opposed to non-violent persons with schizophrenia (NVS) hypoactivated their inferior parietal lobe. When anticipating shock, VS versus NVS hyperactivated their medial prefrontal gyrus, cuneus, middle temporal gyrus and middle occipital gyrus. When viewing negative emotional pictures, VS versus NVS hyperactivated the middle frontal gyrus, inferior frontal gyrus, anterior cingulate, lingual gyrus, precentral gyrus, globus pallidus, mid-cingulate, and precuneus. Limitations. Due to the small number of available studies, sample overlap and insufficient reporting of relevant moderators we could not conduct a meta-analysis. Conclusions. We found nonsystematic functional correlates of aggression in schizophrenia. Only few studies using varied paradigms and often overlapping samples have been conducted. There have been no attempts to replicate any of the observed findings in the published literature. Focusing on future directions, we recommend that authors adhere to clear definitions of aggression, measurements of psychopathology, comorbidities and medication. In particular, replication studies would allow for a better synthesis of the findings. (PROSPERO registration number: CRD42016048579)